Analisa Karakteristik Penggaturan Kerja Operator Terhadap Pencapaian Keluaran Produksi - edy edy (Universitas Harapan Medan, 2019)
This research is to find out the characteristics of one of the companies taken in one journal that shows the 100% display check output data in a period of 1 week, summary output from 5 operators in 1 week and summary of output / day and number of types of output checked / days. Where the results obtained have differences in suitability of the operators doing work in the week. So by analyzing the 100% display checking process, we will find the causes of output variations and possible ways to minimize the output variation. By reducing the output variation, it is expected that the output of 100% checking will be more stable and increase compared to the previous output. The end result is customer satisfaction with the fulfillment of customer demand for goods ordering and reduction in the company's operational costs related to the reduction in the number of employees